Individual Morality and Internal Control Systems on Indications of Fraud Prevention in Village Financial Management in Indonesia: A Literature Review - Dewi A., Putu Anesya (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
Examining the role of individual morality in the internal control system’s ability to eliminate fraud in the management of village finances was the primary objective of this research. In order to avoid fraud, this study surveyed prior work on the topics of individual ethics and internal control systems. In this essay, screening, inclusion, and exclusion were used. An analysis of 20 publications revealed that internal control mechanisms and personal morale are critical to preventing fraud. This indicates that there is a significant influence of the internal control system and individual morality in preventing fraud in village financial management.